A Qualitative Exploration of Factors Influencing Physical Activity Behaviour for Individuals with Parkinson's Disease Using the Social Ecological Model - Bradley MacCosham; Evan Webb; Wahid Hamidi; Jessica Oey; Francois Gravelle (European Federation of Adapted Physical Activity, 2021)
Physical activity (PA) can benefit individuals with Parkinson's disease (PD), however, many individuals tend to be sedentary. This qualitative study explored factors influencing PA behaviour for individuals with PD using the social ecological model. Twelve individuals with PD took part in semi-structured interviews. Data were thematically analysed. Results suggest that individuals with PD experience several constraining and facilitating factors to PA behaviour. Intrapersonal constraints revolved around uncertainties that PA is beneficial for individuals with PD, a lack of interest in available PA programs, and disease-specific issues whereas intrapersonal facilitators included prior experiences of enjoyment in PA, seeing improvements, and wanting to maintain independence. Interpersonal constraints related to lacking social support and perceived stigma whereas interpersonal facilitators were, passionate PA program staff, and being active with similar others. Environmental constraints pertained to PA programs failing to adapt program activities, lack of time, and transportation accommodations, whereas environmental facilitators were exposure to non-traditional PA programs, access to resources on PA, and accessibility to community PA programs. Findings highlight the need to address factors influencing PA behaviour for individuals with PD.